Pengaruh Leverage dan Kompleksitas Operasi terhadap Audit Delay dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Heni, Heni (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of leverage and operating complexity on audit delay, with firm size as a moderating variable, in mining-sector companies listed on the Indonesia Stock Exchange during the 2018–2020 period. The study employs a quantitative approach using secondary data obtained from annual financial statements and audited financial reports. The sample was selected through purposive sampling and consisted of 41 companies, resulting in 123 firm-year observations. Data were analyzed using panel-data regression and Moderated Regression Analysis with EViews version 10. The results show that leverage has a negative and significant effect on audit delay, while operating complexity has no significant effect. Firm size significantly moderates and strengthens the relationship between leverage and audit delay. However, firm size is unable to moderate the relationship between operating complexity and audit delay. The moderated model explains 11.36% of the variation in audit delay, while the remaining 88.64% is explained by other factors outside the research model.